PENGARUH LINGKUNGAN RUMAH SAKIT SERTA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA TENAGA KESEHATAN DI RUMAH SAKIT XYZ DKI JAKARTA [THE INFLUENCE OF THE HOSPITAL ENVIRONMENT AND TRANSFORMATIONAL LEADERSHIP ON THE PERFORMANCE OF HEALTH WORKERS AT XYZ DKI JAKARTA HOSPITAL] - Setiawan, Iwan (Universitas Pelita Harapan, 2024)
The purpose of this study is to explain the influence of the hospital environment and transformational leadership on the performance of health workers (inpatient nurses). The phenomenon that occurs is the level of complaints of patients and families of patients over inpatient nurse services by 60% of 30 respondents to the exploration study. The quantitative study was applied in research at XYZ private hospital located in DKI Jakarta. The respondents were 160 inpatient nurses who had been permanent employees for more than two years. Data collection through questionnaire measuring tools with Likert scale 1 – 5. Data analysis applies the Structural Equaition Model and data processing with SmartPLS. The results show that the hospital environment, transformational leadership has a positive effect on the performance of health workers. Research contributions can be used as reference material for private hospitals to improve the performance of health workers.Bahasa Indonesia Abstrak: Tujuan penelitian ini ingin menjelaskan pengaruh dari lingkungan rumah sakit dan kepemimpinan transformasional terhadap kinerja tenaga kesehatan (perawat ruang rawat inap). Fenomena yang terjadi tingkat keluhan pasien dan keluarga pasien atas layanan perawat rawat inap sebesar 60% dari 30 orang responden studi eksplorasi. Studi kuantitatif diterapkan dalam penelitian di Rumah Sakit swasta XYZ yang berada di DKI Jakarta. Responden adalah 160 orang perawat ruang rawat inap yang sudah menjadi pegawai tetap lebih dari dua tahun. Pengumpulan data melalui alat ukur kuisioner dengan skala likert 1 – 5. Analisis data menerapkan Structural Equaition Model dan pengolahan datanya dengan SmartPLS. Hasil menunjukkan bahwa lingkungan rumah sakit, kepemimpinan transformasional berpengaruh positif terhadap kinerja tenaga kesehatan. Kontribusi penelitian dapat dijadikan bahan referensi untuk rumah sakit swasta demi meningkatkan kinerja tenaga kesehatan